The Role of Arabic in Increasing Local Tourism Attraction in Aceh: Peran Bahasa Arab dalam Meningkatkan Daya Tarik Pariwisata Lokal di Aceh - Muhammad Darda; Akmal Fajri (Pusaka Cendekia Indonesia Foundation, 2025)
This study aims to analyze the strategic role of the Arabic language in enhancing the appeal of local tourism in Aceh, particularly in the development of halal tourism. The research method used is descriptive qualitative with a library research approach. Data were obtained from various scholarly sources, including journals, books, articles, and official documents. The findings show that the use of Arabic in tourism promotion, services, and communication can improve the comfort and trust of Muslim tourists, especially from Arabic-speaking countries. One of the regions with significant potential for developing Islamic tourism in Aceh is Subulussalam City. With religious sites such as the tomb of Sheikh Hamzah Fansuri and the Grand Mosque of Subulussalam, the city has an opportunity to emerge as an alternative halal tourism destination. However, the limited Arabic proficiency among local tourism actors remains a key challenge. Therefore, integrating Arabic into vocational education, providing industry-based training, and developing Arabic-language digital promotional media are necessary to support Aceh including Subulussalam as a leading halal tourism destination in Southeast Asia. Penelitian ini bertujuan untuk menganalisis peran strategis bahasa Arab dalam meningkatkan daya tarik pariwisata lokal di Aceh, khususnya dalam konteks pengembangan wisata halal. Penelitian ini menggunakan metode kualitatif deskriptif dengan pendekatan studi pustaka. Data diperoleh dari berbagai literatur ilmiah, seperti jurnal akademik, buku, artikel, dan dokumen resmi yang relevan. Hasil kajian menunjukkan bahwa penggunaan bahasa Arab dalam promosi, pelayanan, dan komunikasi pariwisata dapat meningkatkan kenyamanan serta kepercayaan wisatawan Muslim, terutama dari negara-negara berbahasa Arab. Salah satu daerah yang memiliki potensi besar dalam pengembangan wisata religi di Aceh adalah Kota Subulussalam. Dengan keberadaan situs-situs Islam seperti makam Syekh Hamzah Fansuri dan Masjid Agung Subulussalam, kota ini memiliki peluang menjadi destinasi wisata halal alternatif. Namun, keterbatasan penguasaan bahasa Arab di kalangan pelaku wisata lokal masih menjadi kendala utama. Oleh karena itu, diperlukan integrasi bahasa Arab dalam pendidikan vokasi, pelatihan industri, serta pengembangan media promosi digital berbahasa Arab guna mendukung posisi Aceh, termasuk Subulussalam, sebagai destinasi wisata halal unggulan di Asia Tenggara.